Produção e comercialização de produtos de base ecológica: políticas públicas e atuação das cooperativas de assentados da reforma agrária - Sandri, Alexandre Maurício (2019)
Governmental incentive by means of policy-making and its implementation is an important supporting tool to the development of the countryside, above all to those intended to family farming and land reform settlements. In this respect, government schemes (PAA, PNAE, ATES and Terra Sol) designed to address land reform settlers through their organizations (agricultural cooperatives and associations) become relevant to the growth of the settled communities. The absence or the lack of continuity of these policies may affect overmuch the feasibility and the subsistence of these communities hindering the economic and social development of the settled farmers. The goal of this study is to analyze the different circuits used by the land reform settlers’ cooperatives of Paraná that have in view the production and trading of organic products (ecological base) yielded by the cooperative members fostered by public policies. It attempts to address the following research question: to what extent public policies add to the development of the production and trading of ecological base foods in the land reform settlers’ cooperatives of Paraná? The methodology includes the following research strategies: a semi-structured questionnaire applied to the managers of 10 settlers’ cooperatives; face-to-face interviews with organic certified farmers from the settlements affiliated to the cooperatives Terra Livre (Lapa) and Dorcelina Folador (Arapongas) and a bibliometric review of the researched topic. Google Forms and Microsoft Excel were used to draw the charts and tables and present the data. There is evidence through this field research backed by bibliographic reference and specific legislation that public policies are of paramount importance having a positive impact in the lives of the communities. This dissertation infers that the absence or cut back on governmental programs bring about limitation to the organic/ecological production system employed by the settlers, causing cooperatives, responsible for the production and logistics of the settlements production, to lose ground.